Acute Abdomen Secondary to a Spontaneous Perforation of the Biliary Tract, a Rare Complication of Choledocholithiasis - Gómez-Torres, G.A. (Int J Surg Case Rep, 2017)
INTRODUCTION: The spontaneous perforation of the biliary tract (SPBT) is an extremely rare cause of peritonitis, which was first described by Freeland in 1982, to date only around 70 cases have been reported. Here we present a case of spontaneous perforation of the biliary tract, in a patient with choledocholithiasis, which was treated with ultrasound-guided drainage and ERCP. CASE REPORT: A 51-year-old male was admitted to the emergency room for 15-day evolution jaundice, localized pain in the right flank and hypochondrium of 3 days. He had a history of cholecystectomy 15 years ago and 4 episodes of cholangitis, the last one in 2015. A magnetic resonance imaging (MRI) was performed, that showed evidence of choledocholithiasis, in addition to a possible biliary leakage. The patient was treated with ultrasound-guided drainage and ERCP successfully. DISCUSSION: Spontaneous perforation of the biliary tract is a disease entity in which wall of the extrahepatic or intrahepatic duct is perforated without any traumatic or iatrogenic injury. The clinical presentation varies from nonspecific abdominal pain to biliary peritonitis, in most of the cases forming bilomas. Universal management involves decompression of the biliary tree and repair of the leak site. CONCLUSION: The spontaneous perforation of the biliary tract is a disease that represents a diagnostic challenge. The treatment in the patients with SPBT is not well established and has to be individualized for each case, depending on the history of the patient, the site of perforation, the time of evolution, the suspicion of infection, and the patient status.